A Critical Review on the Existing Wastewater Treatment Methods in the Covid-19 Era: What Is the Potential of Advanced Oxidation Processes in Combatting Viral Especially Sars-Cov-2? - Sandoval, A; Sandoval, A (Elsevier Ltd, 2022)
The COVID-19 epidemic has put the risk of virus contamination in water bodies on the horizon of health authorities. Hence, finding effective ways to remove the virus, especially SARS-CoV-2, from wastewater treatment plants (WWTPs) has emerged as a hot issue in the last few years. Herein, this study first deals with the fate of SARS-CoV-2 genetic material in WWTPs, then critically reviews and compares different wastewater treatment methods for combatting COVID-19 as well as to increase the water quality. This critical review sheds light the efficiency of advanced oxidation processes (AOPs) to inactivate virus, specially SARS-CoV-2 RNA. Although several physicochemical treatment processes (e.g. activated sludge) are commonly used to eliminate pathogens, AOPs are the most versatile and effective virus inactivation methods. For instance, TiO2 is the most known and widely studied photo-catalyst innocuously utilized to degrade pollutants as well as to photo-induce bacterial and virus disinfection due to its high chemical resistance and efficient photo-activity. When ozone is dissolved in water and wastewater, it generates a wide spectrum of the reactive oxygen species (ROS), which are responsible to degrade materials in virus membranes resulting in destroying the cell wall. Furthermore, electrochemical advanced oxidation processes act through direct oxidation when pathogens react at the anode surface or by indirect oxidation through oxidizing species produced in the bulk solution. Consequently, they represent a feasible choice for the inactivation of a wide range of pathogens. Nonetheless, there are some challenges with AOPs which should be addressed for application at industrial-scale. © 2022